Coupling of the Subpolar Gyre and the Overturning Circulation During Abrupt Glacial Climate Transitions - Klockmann, M.; Mikolajewicz, U.; Kleppin, H.; Marotzke, J.; 1 Max Planck Institute for Meteorology Hamburg Germany; 3 MARUM Bremen Germany (Geophysical Research Letters, 2020)
We present a mechanism for self‐sustained ocean circulation changes that cause abrupt temperature changes over Greenland in a multimillennial climate model simulation with glacial CO2 concentrations representative of Marine Isotope Stage 3. The Atlantic meridional overturning circulation (AMOC) and the subpolar gyre (SPG) oscillate on millennial time scales. When the AMOC is strong, the SPG is weak and contracted; when the AMOC is weak, the SPG is strong and extensive. The coupling between the two systems via wind‐driven and density‐driven feedbacks is key to maintaining the oscillations. The SPG controls the transport of heat and salt into the deep‐water formation sites and thus controls the AMOC strength. The strength and location of the deep‐water formation affect the density‐driven part of the SPG and thus control the mean strength and extent of the SPG. This mechanism supports the hypothesis that coupled ocean‐ice‐atmosphere interactions could have triggered abrupt glacial climate change. Plain Language Summary: Between 57.000 and 29.000 years ago, the last glacial period was marked by several abrupt warming and cooling events over Greenland and the North Atlantic. Understanding the mechanism behind these so‐called Dansgaard‐Oeschger events increases our understanding of possible tipping points that cause abrupt change in the Earth system. The role of the ocean in causing these events is still a topic of debate. We find abrupt changes in the North Atlantic circulation that resemble Dansgaard‐Oeschger events in a simulation with a state‐of‐the‐art climate model. These simulated ocean circulation changes are generated without adding external triggers such as meltwater from glaciers. Instead, the events are generated by the interaction of the two large‐scale current systems in the North Atlantic—the Atlantic meridional overturning circulation (AMOC) and the North Atlantic subpolar gyre (SPG). Both current systems are affected by changes in surface winds and the density pattern of the North Atlantic. We find ...